2012
DOI: 10.1111/j.1468-1293.2011.00977.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiretroviral therapy prescribing in hospitalized HIV clinic patients

Abstract: ObjectivesAntiretroviral therapy (ART) medication prescribing errors in hospitalized patients still remain common. This study aimed to examine the initial prescribing of antiretroviral drug regimens for HIV clinic patients admitted to an urban academic teaching hospital. MethodsA retrospective chart review of all patients with a discharge diagnosis of HIV or AIDS was performed. Only patients actively managed by the hospital out-patient HIV clinic at the time of discharge were included in the final analysis. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 20 publications
0
24
0
2
Order By: Relevance
“…1,2,[4][5][6][7][8] The most common type of ARTrelated error observed among patients in the current study was drug-drug interaction between ART and other medications. The majority of drug-drug interactions were between atazanavir/nelfinavir and gastric acid suppressants (namely, proton pump inhibitors and histamine 2 receptor antagonists).…”
Section: Discussionmentioning
confidence: 94%
“…1,2,[4][5][6][7][8] The most common type of ARTrelated error observed among patients in the current study was drug-drug interaction between ART and other medications. The majority of drug-drug interactions were between atazanavir/nelfinavir and gastric acid suppressants (namely, proton pump inhibitors and histamine 2 receptor antagonists).…”
Section: Discussionmentioning
confidence: 94%
“…Hospitalization often interrupts care continuity and contributes to polypharmacy in the general population [2]. Hospitalization occurs more frequently among those with HIV [132], and represents a high-risk time for medication errors [133135]. …”
Section: Factors Contributing To Polypharmacy’s Harmsmentioning
confidence: 99%
“…Studies at other large hospitals have shown HIV medication error rates ranging from 22 to 86% . These studies have found errors in nearly every aspect of medication management, ranging from ineffective antiretroviral regimens, improper dosages, incorrect frequencies, failure to adjust doses for comorbid disease states, and numerous drug interactions both with medications for separate conditions and with other antiretrovirals .…”
Section: Introductionmentioning
confidence: 99%